Implementation of Business Competition Compliance Program to Prevent Unfair Business Competition Practices Against Business Enterprises - Hartini, Rahayu; Arief, Muhammad; Permana, Adi (Audito Comparative Law Journal (ACLJ), 2024)
This research is motivated by the government's seriousness in realizing improvements in the community's economy, namely by creating a business competition compliance program to overcome or prevent unfair business competition practices among business people. The effectiveness and efficiency of the implementation of the program, it is still not fully realized, because there are still many companies that have not participated in the business competition compliance program. The legal issues in this research are: 1). Reviewing the supervisory role of KPPU on the effectiveness of the business competition compliance program in efforts to prevent unfair business competition. 2. Analyze the strategies for dealing with unfair business competition and implementing business competition compliance programs in society. This research is normative juridical. By using a statutory and conceptual approach. In this study, two sources of primary and secondary legal materials were used.. This institution has a very broad authority, namely being a supervisory institution, it also has authority in the judicial and legislative fields. One of the legislative powers issued is KPPU Regulation Number 1 of 2022 concerning the Business Competition Compliance Program. This program is expected to be a form of effort to prevent unfair business competition. In practice this program is still not effective. Therefore, it is necessary to revise Law Number 5 of 1999 so that it will provide a clear position for KPPU in carrying out its duties and be able to implement business competition compliance programs to the fullest. Second, regarding the strategy developed to create fair business competition, it can provide understanding for business actors to comply with and also build awareness independently to help implement the program and to be able to identify, assess and manage risks that will occur with the provision of mentoring.